The Bank for the Accounts of Companies Harmonized (BACH) database - Alina Tarta; Ana Margarida de Almeida; Antonio De Socio; Bego\~na Gutiérrez del Olmo; Bozena Wtulich; Cécile Buydens; Chantal Lemmens-Dirix; Christophe Cahn; Ewa Sokolowska; Fábio Albuquerque; Fabrizio Balda; Franck Lemaire; et al. (European Central Bank (ECB), 2015)
The Bank for the Accounts of Companies Harmonized (BACH) is a free-of-charge database containing the aggregated accounting data of non-financial incorporated enterprises for, so far, 11 European countries. While the individual accounts feeding the database were originally prepared in line with national accounting standards consistent with European Accounting Directives, they have been harmonised with a view to preserving, to the greatest extent possible, the cross-country comparability of the resulting data. This article presents the methodology underpinning BACH, including the content of the database. It describes the characteristics of national samples and outlines the harmonisation process. BACH is a unique tool for analysing and comparing the financial structure and performance of firms across European countries. A simple case study is also presented in support.
Keywords: C81; M41; 330; accounting standards; annual individual accounts; European non-financial corporations; statistics